Role of Festivals & Events In Development of Tourism at Gujarat: Exploring the Impact of Festivals and Events on Tourism Development in Gujarat (Journal of Advances and Scholarly Researches in Allied Education, 2015)
A tourism best practice is an innovative policy,strategy, programme, process or practice that is shown to produce superiorresults. Documented best practices are useful in formulation of tourismstrategies to improve the tourism performance through increasedcompetitiveness. The sharing of Best Practices allows State Governments to consider how to adapt the experiences of other states inplanning, marketing, maintenance and implementation of the tourism developmentplan for their states. The Department of Tourism in the states hasresponsibility for implementation of tourism projects funded by the Departmentof Tourism, Government of India and the projects identified by them under theirrespective state tourism policy. The tourism industry of India is economically importantand grows rapidly. The World Travel & Tourism Council calculated thattourism generated INR6.4 trillion or 6.6% of the nation’s GDP in 2012. Itsupported 39.5 million jobs, 7.7% of its total employment. The sector ispredicted to grow at an average annual rate of 7.9% from 2013 to 2023. Thisgives India the third rank among countries with the fastest growing tourismindustries over the next decade. India has a large medical tourism sector whichis expected to grow at an estimated rate of 30% annually to reach about 95billion by 2015. This paper discusses how India is emerging as a populartourist destination in the world, driven by the focus on innovation andcreating value for tourists. It aimed change the attitude and behavior towardforeign tourists by stressing on the aspect that a guest has been held in highesteem in India since ancient times. It also examines the impact of India’seconomic growth on tourism, Contributors to economic growth, Role of Tourismindustry in India’s GDP, Foreign versus Domestic Tourists. The paper alsoexplores that there has been a tremendous growth in tourism in India because ofthe policies of the government and support from all levels. Tourism isconsidered to be an economic bonanza. It is a multi-segment industry. Whilegauging the positive economic effects of tourism, we study its contribution to thegeneration of national income, expansion of employment opportunities, rising oftax revenue, generation of foreign exchange .and transformation of regionaleconomy. Travel & Tourism is an important economic activity in mostcountries around the world. As well as its direct economic impact, the industryhas significant indirect and induced impacts. Indian Tourism offers a potpourriof different cultures, traditions, festivals, and places of interest. There area lot of options for the tourists. India is a country with rich cultural andtraditional diversity. This aspect is even reflected in its tourism. Thedifferent parts of the country offer wide variety of interesting places tovisit.